Cross-linking process of cis-polybutadiene rubber with peroxides studied by two-dimensional infrared correlation spectroscopy: a detailed tracking1. Issue 14 (19th February 2015) - Liu, Xifei; Zhou, Tao; Liu, Yongcheng; Zhang, Aiming; Yuan, Canyao; Zhang, Weidong
<x xml:space="preserve">Abstract</x> Detailed mechanism of cis-BR cross-linking with peroxides was studied using PCMD2D and 2D correlation FTIR, and a 5-step process was determined.